Industrial and Labor Economics Issues in Developing and Transition Countries - Kar, Saibal; Datta, Debabrata; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2015)
This book is an attempt to capture and analyze several idiosyncratic features of industry and labor in the developing world. Available books and graduate-level texts in labor economics largely discuss industrial and labor market situations prevalent in developed countries, where well-defined institutional arrangements and regulations create a very different scope of analysis. The patterns of choice in training and contracts in the labor market more apparent in developing and transition countries are discussed, as are the information-theoretic results. The book also critically examines labor migration, a context in which the developing and transition countries represent large sources in the present global order. A broad base of empirical observations from industries is used to develop analytical conjectures on risk-sharing arrangements between workers and employers, while strong intuitive explanations are combined with relevant mathematical and graphical derivations, ensuring the book$1 (Bs readability among graduate students pursuing courses in labor economics and industrial economics for developing and transition countries. The book may also serve as a valuable reference guide for all students in advanced human resources courses at management schools. Presenting state-of-the art research findings in all of its chapters, the book discusses numerous institutional peculiarities of the developing world, making the results distinct in view of the general scope of labor economics.s
Chapter 1. The Dimensions of Labor Market in Developing and Transition Countries -- Chapter 2. Labor Markets in Developing and Transition Countries -- Chapter 3. Asymmetric Information in the Labor Market -- Chapter 4. Risk Sharing and Rent Sharing in the Labor Market -- Chapter 5. Industrial Organization and the Labor Market -- Chapter 6. Labor Unions: Concepts, Models and Public Policies.
Keywords: Personnel management; Industrial organization; Labor economics; Population; Emigration and immigration; Economics; Labor Economics; Industrial Organization; Human Resource Management; Migration; Population Economics; Electronic books